Step into STEAM : your standards-based action plan for deepening MATHEMATICS and SCIENCE learning grades K-5 - Bush, Sarah B. (Thousand Oaks : Corwin, 2019)
Create meaningful and transformative K-5 STEAM learning experiences for each and every student Make the most of your limited instructional time and become part of the Step into STEAM movement! Seamlessly design and implement K-5 STEAM inquiries that align carefully to key mathematics and science content and practices and prepare elementary students for their bright futures. Taking an opposite approach to existing resources that provide collections of disjointed STEAM activities, this book empowers teachers and schools to build cohesive and sustainable STEAM infrastructures-grounded in grade-level standards and purposeful assessment-to deepen the mathematics and science learning of each and every student.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Mathematics -- Study and teaching (Elementary) -- United States; Science -- Study and teaching (Elementary) -- United States; Mathematics -- Study and teaching; Science -- Study and teaching -- Standards -- United States